Faktor-Faktor Yang Mempengaruhi Penerimaan Opini Audit Going Concern - Khalita, Roselina; Challen, Auliffi Ermian (Information Technology and Science (ITScience), 2022)
This research was conducted with the aim of examining the effect of company growth, financial distress, and disclosure on going concern audit opinion acceptance. This research was conducted using logistic regression method. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange. Sampling with a total of 95 companies was carried out by using purposive sampling technique. While the analysis was carried out by descriptive statistical test and logistic regression test. Based on the data analysis conducted in this study, it can be concluded that company growth has no effect on going concern audit opinion acceptance. Financial Distress has a positive effect on going concern audit opinion acceptance. Disclosure has a negative effect on going concern audit opinion acceptance